Determination of Firm Value with Investment Decisions as an Intervening Variable (Case Study at UMA) - Satria, Edo; Nawir, Jubaedah; Mulyantini, Sri (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to examine the influence of company size, profitability, and financial risk on firm value, with investment decisions serving as an intervening variable. The population for this research comprises 105 multi-sector companies listed on the Indonesia Stock Exchange. The study employs a full sampling method, covering the year 2022 with a total of 105 observations. Data were analyzed using cross-sectional regression processed through E-Views version 13. The results reveal the following: (1) Company size negatively affects firm value; (2) Profitability negatively affects firm value; (3) Financial risk positively affects firm value; (4) Investment decisions positively affect firm value; (5) Company size does not indirectly affect firm value through investment decisions; (6) Profitability does not indirectly affect firm value through investment decisions; (7) Financial risk does not indirectly affect firm value through investment decisions.